Transforming Quality And Patient Safety Through Healthcare Facility Accreditation: A Systematic Review - Muhammad Iqbal Maulana; Siswanto Pabidang (International Journal of Health Engineering and Technology, 2026)
Healthcare facility accreditation has been widely adopted as an external mechanism for quality assurance and patient safety improvement. However, evidence on its real-world effectiveness remains fragmented across diverse settings, accreditation bodies, and outcome measures. This systematic review aimed to synthesize available evidence on the impact of hospital accreditation programs on the quality of care and patient safety outcomes, comparing accredited with non-accredited hospitals or pre-accreditation status. We searched PubMed, Scopus, Epistemonikos, Cochrane Library, Web of Science, and Google Scholar for quantitative studies published from April 2000 until April 2026. Two independent reviewers screened studies and extracted data. Quality appraisal was conducted using the Newcastle–Ottawa Scale (NOS), ROBINS-I, and the Critical Appraisal Skills Programme (CASP) tool. Twenty-one studies from 13 countries met the inclusion criteria, encompassing cross-sectional surveys, quasi-experimental designs, interrupted time series, longitudinal studies, and qualitative case studies. Evidence predominantly favored accreditation, demonstrating consistent improvements in clinical process quality, patient safety culture, and patient satisfaction. Quasi-experimental and longitudinal designs provided the strongest evidence. Barriers included resource constraints, staff resistance, and variability in leadership engagement.  Accreditation is a promising driver of quality and patient safety improvement in hospital settings, particularly when coupled with strong organizational leadership and adequate resourcing. Future research should employ more rigorous study designs and standardized outcome metrics to strengthen the evidence base.